Acroptilon repens induces apoptosis in human breast adenocarcinoma - Mosaddegh, Mahmoud; Irani, Mahboobeh; Hamzeloo-Moghadam, Maryam (Bangladesh Journal of Pharmacology, 2018)
Evaluating the effect of herbal extracts has been always interesting for cancer researchers considering that these natural materials could be suitable sources for finding new anti-cancer agents. In the present study, Acroptilon repens methanol extract had been evaluated for its cytotoxic effects in two human breast cancer cell lines, MCF-7 and MDA-MB-468, using MTT assay. The apoptosis potential had also been evaluated using annexin-V/propidium iodide assay, Hoechst 33258 staining and evaluating the cell cycle with flow cytometery. The MTT results showed cytotoxicity with IC50 values of 69.2 and 32.6 μg/mL for MCF-7 and MDA-MB-468 cells, respectively. The results of the apoptosis assays confirmed the apoptosis potential of the plant extract in the breast cancer cell lines suggesting A. repens for further cancer studies. Video Clips of Methodology: Adding cell suspensions to the wells: 1 min 02 sec Click to watch Preparing different concentrations: 1 min 36 sec Click to watch Removing medium containing MTT: 0 min 53 sec Click to watch Adding DMSO at the final step: 0 min 45 sec Click to watch Recording the absorbance of formazan crystals: 0 min 32 sec Click to watch